The coronavirus conundrum – Variants and vaccines – The pregnant woman and her child - Pacheco-Romero, José (2021)
In late 2020, vaccines developed in the Western world against the SARS-CoV-2 virus were approved and are currently being inoculated, together with Chinese and Russian vaccines. In the meantime, we are in a second wave of the disease and the new coronavirus has been transforming to allow for better propagation, harboring and replication in humans. The disease now manifests itself with new symptoms, greater contagiousness, severity and variation in the number of deaths. Coronavirus infection of pregnant women is occurring with harshness and maternal and perinatal consequences. Vaccination has been initiated in pregnant women and nursing mothers, after discussion with their gynecologists about risks and benefits. This article provides a brief account of the events that took place during the transition from 2020 to 2021.